Effects of Ear Acupuncture Therapy for Obesity on the Depression of Obese Women. Issue 5 (October 2014) - Set, Turan; Cayir, Yasemin; Pirim, Asuman Bihter Guven
Background: Obesity is one of the leading health risks worldwide, and depression is among the leading causes of the burden of disease. These disorders are increasingly prevalent as comorbidities. Depressive symptoms are associated with obesity, and are more common in women. Objective: To evaluate the effectiveness of ear acupuncture for obesity on the depression of obese women. Methods: After baseline testing, 30 eligible patients with body mass index (BMI) >29.9 kg/m 2 were included. The Beck Depression Inventory for Primary Care (BDI-PC) was used to assess changes in depression. BMI was also measured. Patients had six ear acupuncture sessions, every 15 days and were followed up for 3 months. Twenty four patients completed the study. Results: The mean±SD age of patients was 42.9±9.0 years. Their mean±SD BMI was 39.0±4.7 kg/m 2 before acupuncture, decreasing to 37.2±4.3 kg/m 2 after acupuncture therapy (p<0.001). The mean depression score was 4.4±2.3 before acupuncture, decreasing to 2.7±1.4 (p<0.001) after treatment. There was no significant correlation between BMI and depression score before acupuncture therapy (p=0.104). After acupuncture therapy, no significant correlation was found between the percentage reduction of BMI and percentage reduction of the depression score (p=0.119). Conclusions: Further research into the effects of ear acupuncture in the management of obesity and depression is justified.